Carbon dioxide electroreduction catalyst based on bionic proton rejection layer as well as preparation method and application of carbon dioxide electroreduction catalyst

By forming a bionic proton repelling layer on the surface of the carbon dioxide electroreduction catalyst, the problems of hydrogen evolution reaction and carbonate precipitation in the carbon dioxide electroreduction reaction in the acidic medium are solved, and efficient and sustainable CO2 reduction effect is achieved.

CN119663345APending Publication Date: 2025-03-21QILU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814360.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In acidic media, the electroreduction reaction of carbon dioxide faces competition in hydrogen evolution reactions and carbonate precipitation problems, resulting in low selectivity and efficiency and short reactor service life.

Method used

The carbon dioxide electroreduction catalyst based on a bionic proton repelling layer is used. The bionic proton repelling layer prepared by a cationic surfactant is coated with a nanotriangle gold catalyst, simulating the proton barrier mechanism in biological systems, inhibiting the hydrogen evolution reaction and avoiding carbonate precipitation.

Benefits of technology

It significantly improves the selectivity and efficiency of CO2 reduction reaction, extends the service life of the reactor, and achieves efficient and sustainable CO2 reduction under strong acidic conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663345A_ABST
    Figure CN119663345A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide electroreduction catalyst based on a bionic proton rejection layer as well as a preparation method and application of the carbon dioxide electroreduction catalyst, and relates to the technical field of electrocatalysis. The carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer comprises the bionic proton exclusion layer and an active substance wrapped in the bionic proton exclusion layer, the active substance is a nano triangular gold catalyst, and the bionic proton exclusion layer is prepared from a cationic surface active agent. Meanwhile, the active substance is coated with the bionic proton rejection layer, so that the hydrogen evolution reaction in an acid medium can be remarkably inhibited, the selectivity and efficiency of CO2 reduction reaction are improved, meanwhile, the proton barrier mechanism in a biological system can be simulated by utilizing the bionic proton rejection layer, the precipitation problem caused by alkali metal cations is avoided, and the sustainability of the reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalysis, and in particular to a carbon dioxide electroreduction catalyst based on a bionic proton repelling layer, and a preparation method and application thereof. Background Art

[0002] In the field of electrocatalysis, carbon dioxide (CO 2 ) electroreduction reaction (CO 2 R) is one of the important technologies to achieve carbon neutrality and efficient use of renewable energy. However, CO 2 Electroreduction has significant challenges, mainly including the strong competition of hydrogen evolution reaction (HER) and CO 2 The non-polarity and chemical inertness of the molecule. 2 It is difficult for R catalysts to achieve high selectivity and high efficiency under acidic conditions because the hydrogen evolution reaction tends to take precedence at lower overpotentials, which significantly reduces the CO 2 In addition, the surface of traditional catalysts usually lacks repulsion to protons and cannot effectively inhibit HER, resulting in poor selectivity of the reduction product.

[0003] In order to deal with these problems, the prior art introduces alkali metal cations (such as K + 、Na + ) to inhibit HER while promoting CO 2 However, the addition of alkali metal ions easily leads to the formation of carbonate precipitation in the electrolyte, which in turn shortens the service life of the reactor and limits its sustainability. In addition, although some biomimetic electrocatalytic designs have begun to be applied to CO 2 R, such as improving selectivity by mimicking the proton barrier mechanism of biological systems, but stable and efficient CO in acidic media 2 Reduction catalyst design remains a major technical challenge.

[0004] Therefore, how to develop a bionic design that can be used in CO 2 The catalyst for the electroreduction reaction of 2-hydroxy-2-nitrogen-2-thiocyanate (2-NH4-2-thiocyanate) is used to solve the problem of hydrogen evolution reaction inhibition in acidic media, avoid carbonate precipitation problems, and achieve efficient CO reduction under strong acidic conditions. 2 reduction and other technical issues, thereby significantly improving CO 2 Selectivity, efficiency and sustainability of reduction technologies. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer, and a preparation method and application thereof. The carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer comprises a bionic proton exclusion layer and an active substance coated inside the bionic proton exclusion layer, wherein the active substance is a nano-triangular gold catalyst, and the bionic proton exclusion layer is prepared from a cationic surfactant. At the same time, coating the bionic proton exclusion layer on the active substance can significantly inhibit the hydrogen evolution reaction in an acidic medium, thereby improving the CO 2 The selectivity and efficiency of the reduction reaction are improved. At the same time, the bionic proton exclusion layer can simulate the proton barrier mechanism in the biological system, avoiding the precipitation problem caused by alkali metal cations and improving the sustainability of the reaction.

[0006] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a carbon dioxide electro-reduction catalyst based on a bionic proton exclusion layer, comprising a bionic proton exclusion layer and an active substance coated inside the bionic proton exclusion layer, wherein the active substance is a nano-triangular gold catalyst, and the bionic proton exclusion layer is prepared from a cationic surfactant.

[0007] Preferably, the cationic surfactant is cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB) or polydimethyldiallylammonium chloride (PDDA).

[0008] Preferably, the charge density of the biomimetic proton repelling layer is 10000~20014 C / cm 3 .

[0009] Preferably, the nano-triangular gold catalyst is prepared by the following method: (1) Mix the hexadecyltrimethylammonium bromide solution, KI solution, chloroauric acid solution and NaOH solution to obtain a mixed solution; (2) adding ascorbic acid solution to the mixed solution, and then adding NaOH solution until the solution becomes colorless to obtain a gold nanotriangle catalyst dispersion; (3) After the nano-triangular catalyst dispersion is allowed to stand, it is purified and centrifuged, and the precipitate after centrifugation is collected, which is the nano-triangular gold catalyst AuNTs.

[0010] Further preferably, in step (1), the cetyltrimethylammonium bromide solution is prepared by mixing 0.1 M cetyltrimethylammonium bromide stock solution and water in a volume ratio of (1.5-1.8):8.

[0011] Further preferably, in step (1), the volume ratio of the hexadecyltrimethylammonium bromide solution, the KI solution, the chloroauric acid solution and the NaOH solution is (9.5-9.8) mL: (70-80) μL: 80 μL: (20-21) μL.

[0012] More preferably, the concentration of the KI solution is 0.01M, the concentration of the chloroauric acid solution is 25.4mM, and the concentration of the NaOH solution is 0.1M.

[0013] Preferably, in step (2), the volume ratio of the mixed solution, ascorbic acid solution and NaOH solution is (9-10) mL:80 μL:10 μL.

[0014] Preferably, in step (2), the concentration of the ascorbic acid solution is 0.064 M and the concentration of the NaOH solution is 0.1 M.

[0015] Preferably, in step (3), the standing time is 24-40 hours.

[0016] Preferably, in step (3), the purification treatment is: repeatedly centrifuging and resuspending the suspension after standing to remove impurities with irregular morphology and substances that do not participate in the reaction.

[0017] The second aspect of the present invention provides a method for preparing the carbon dioxide electroreduction catalyst based on the bionic proton-repelling layer, comprising the following steps: The nano-triangular gold catalyst is dissolved in deionized water to obtain a nano-triangular gold catalyst solution; the nano-triangular gold catalyst solution and a cationic surfactant solution are mixed and stirred to obtain a modified solution; and a bionic proton exclusion layer is formed on the surface of the nano-triangular Au catalyst through an electrochemical deposition method or a physical adsorption method, thereby obtaining a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer.

[0018] Preferably, the concentration of the nano-triangular gold catalyst solution is 0.8-1.2 g / mL, and the concentration of the cationic surfactant solution is 0.104-0.207 mM.

[0019] Preferably, the volume ratio of the nano-triangle Au catalyst solution to the cationic surfactant solution is 1:1.

[0020] Preferably, the specific operation of the electrochemical deposition method is: The modified droplets were coated on the electrode substrate and dried to obtain the working electrode; an electrolytic cell was constructed using Ag / AgCl as the reference electrode, Pt as the counter electrode, and 0.1M sulfuric acid as the electrolyte solution; the constant potential was set to -0.5 V (vs Ag / AgCl), and deposition was performed at 20-27°C for 15-25 minutes to form a bionic proton exclusion layer on the surface of the nanotriangular Au catalyst, thereby obtaining a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer.

[0021] Preferably, the specific operation of the physical adsorption method is: apply the modified liquid droplets on the electrode substrate, let it stand for 25-35 minutes, wash and dry, so that a bionic proton exclusion layer can be formed on the surface of the nano-triangular Au catalyst, and a carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer can be obtained.

[0022] Further preferably, the electrode substrate is a gas diffusion electrode (GDE) or a glassy carbon electrode.

[0023] The third aspect of the present invention provides the use of the above-mentioned carbon dioxide electroreduction catalyst based on the bionic proton-repelling layer in the electrochemical reduction of carbon dioxide.

[0024] Beneficial effects of the present invention: The present invention provides a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer, comprising a proton exclusion layer and an active substance coated inside the proton exclusion layer, wherein the active substance is a nano-triangular gold catalyst, and the proton exclusion layer is prepared from a cationic surfactant. The bionic proton exclusion design of the proton exclusion layer can significantly inhibit the hydrogen evolution reaction in an acidic medium, thereby improving the CO 2 The selectivity and efficiency of the reduction reaction can also simulate the proton barrier mechanism in biological systems, avoiding the precipitation problem caused by alkali metal cations and improving the sustainability of the reaction.

[0025] Specifically, the present invention introduces a biomimetic CTAC cationic surfactant layer to imitate the proton barrier mechanism in the biological system, inhibiting the migration of protons to the catalyst surface, thereby effectively inhibiting HER and improving CO 2 The present invention achieves proton rejection through CTAC bionic design without using alkali metal cations, avoiding carbonate precipitation problems, thereby extending the sustainability of the electrolysis reaction and the life of the equipment. In addition, the present invention uses the proton rejection effect of the CTAC bionic layer to make CO 2 The reduction reaction can still proceed efficiently in a strongly acidic environment with a pH of 1, and has a long stable reaction time and high energy efficiency.

[0026] The application prospects of the carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer prepared by the present invention in the field of electrocatalysis, especially in the field of CO 2 The huge potential of reduction reactions can be applied in related fields such as clean energy conversion and carbon neutrality. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : TEM image of the nano-triangular gold catalyst prepared in Example 1; Figure 2 :: Size distribution diagram of the nano-triangular gold catalyst prepared in Example 1; Figure 3 : XRD pattern of the nano-triangular gold catalyst prepared in Example 1; Figure 4 : Schematic diagram of the structure of the carbon dioxide electroreduction catalyst based on the biomimetic proton-repelling layer; Figure 5 : The effective current density and Faraday constant of different catalysts in Experimental Example 1 vary with potential; wherein A is the effective current density versus potential; B is the Faraday constant versus potential; Figure 6 : Stability test diagram of the carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer in Experimental Example 2; Figure 7 : The bionic proton repelling layer with different charge density in Experimental Example 3 has a graph showing the proton mobility, pH and pH at OHP; wherein, A is a graph showing the change of proton mobility with the charge density of the bionic proton repelling layer; b is a graph showing the change of pH with the distance from OHP; C is a graph showing the change of pH at OHP with the electrode potential. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0029] In the prior art, CO is carried out in an acidic medium. 2 Electroreduction has the following disadvantages: 1) In acidic medium, CO 2 R and HER are highly competitive and it is difficult to effectively increase CO 2 1) The use of alkali metal ions can lead to precipitation in the electrolyte, limiting the sustainability of the reaction and the life of the device; 2) There is no reliable solution that can simultaneously achieve efficient proton rejection and CO 2 activation, especially in acidic environments where metal cations are absent.

[0030] Based on this, the present invention provides a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer and a preparation method and application thereof. Figure 4 As shown, the carbon dioxide electroreduction catalyst includes a bionic proton exclusion layer and an active substance coated inside the bionic proton exclusion layer, wherein the active substance is a nano-triangular gold catalyst, and the proton exclusion layer is prepared from a cationic surfactant. The surface of the Au nano-triangle (AuNTs) catalyst is coated with a bionic proton exclusion layer. The bionic proton exclusion layer has a cationic charge density, forming a proton barrier to prevent protons from migrating to the catalyst surface, thereby reducing the occurrence of hydrogen evolution reaction.

[0031] Among them, in the present invention, ascorbic acid is selected as a reducing agent to adjust the reduction rate of gold ions to ensure the formation of a triangular morphology; the reaction temperature determines the nucleation rate of the metal nucleus and the diffusion rate in the subsequent growth process. Higher temperatures usually promote anisotropic growth, thereby forming non-spherical particles such as triangles. The present invention controls the reaction temperature to 25°C, which can promote the preferential growth of specific crystal faces. The adsorption behavior of the stabilizer can selectively stabilize specific crystal faces and inhibit the growth of other crystal faces, thereby forming nanoparticles with specific morphology. The present invention selects hexadecyltrimethylammonium bromide as a stabilizer, which selectively adsorbs on the {111} crystal face, inhibits the growth of other crystal faces, and thus forms triangular particles. The length of the reaction time determines the degree of crystal growth. Properly extending the reaction time can enhance the preferential growth of anisotropic crystal faces and ultimately form triangular particles. The present invention ensures that the nucleus grows fully without excessive aggregation or dissolution by optimizing the reaction time. The pH value of the solution affects the coordination state and reduction kinetics of the gold ions, thereby affecting the formation of the morphology. By adjusting the acidity and alkalinity of the solution, precise control of crystal growth can be achieved. Generally speaking, weak acid or neutral conditions are more conducive to the formation of triangular morphology. In summary, the triangular morphology of gold nanoparticles is determined by the comprehensive regulation of reaction conditions, especially the type and concentration of reducing agent, the choice of stabilizer, reaction temperature and time, etc. These parameters affect the nucleation and growth dynamics of gold crystals, and ultimately achieve precise regulation of the triangular morphology.

[0032] Through biomimetic design, the proton repelling layer formed by cationic surfactants is used to effectively inhibit the migration of protons and promote CO 2 In addition, the present invention controls the charge density of the biomimetic proton repelling layer to be between 10000 and 20014 C / cm 3 When the range is within 200°, the hydrogen evolution reaction inhibition effect is the best, while maintaining a high CO 2 Reduction efficiency.

[0033] Specifically, the present invention introduces a bionic proton repelling layer on the catalyst surface, which imitates the proton barrier function in the biological system to effectively prevent the migration of protons to the catalyst surface, greatly inhibiting HER, thereby improving CO 2 Compared with the traditional technology, the present invention can reduce the selectivity and efficiency of CO 2 The Faradaic efficiency of the reduction product CO was significantly improved to over 97%.

[0034] In addition, the present invention controls the charge density of the biomimetic proton repelling layer by controlling the concentration of the cationic surfactant. Too high a concentration may lead to a pile-up effect, while too low a concentration may lead to insufficient adsorption. The volume ratio of the nano-triangular gold catalyst and the cationic surfactant solution is controlled to be 1:1 to ensure that the cationic surfactant can be evenly distributed on the surface of the nano-triangular gold catalyst.

[0035] The biomimetic proton exclusion layer achieves proton exclusion in the absence of metal cations, avoiding the precipitation problem, thereby extending the working life of the reactor and improving the sustainability of the reaction. At the same time, it can also ensure the stability of the catalyst in a strong acidic medium, so that the prepared catalyst exhibits extremely high stability and efficiency in a strong acidic environment (pH=1). In a strong acidic medium, the catalyst can continuously perform CO 2 Reduction reaction, and maintain high Faraday efficiency and energy efficiency, with good corrosion resistance and durability. Even in strong acidic conditions, it can continue to work for more than 100 hours and maintain high CO 2 The stable coating structure improves the durability of the catalyst and avoids common corrosion and deactivation problems. In addition, the present invention also avoids the use of alkali metal cations and directly achieves proton rejection through the bionic design of the proton rejection layer, overcoming the problem of shortened reactor life due to carbonate precipitation in the prior art. The application of the bionic proton rejection layer ensures that the catalyst can still efficiently and stably carry out CO reduction in an acidic medium without metal cations. 2 Reduction reaction.

[0036] Compared with the prior art, the present invention achieves a more effective proton rejection function through the biomimetic CTAC layer, without relying on alkali metal cations, and avoids the problem of electrolyte precipitation. In contrast, the prior art relies on cations to inhibit HER, but causes precipitation problems and shortens the life of the reactor. Compared with traditional catalysts, the present invention can significantly improve CO under the same acidic conditions. 2 The efficiency of the reduction reaction, the Faraday efficiency of CO reaches more than 97%, while traditional catalysts are usually lower and have poor stability. In addition, the catalyst of the present invention exhibits extremely high stability and corrosion resistance under strong acidic conditions and can work continuously for a long time.

[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0038] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0039] Example 1: Preparation of nano-triangular gold catalyst AuNTs (1) Add 1.6 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution to 8 mL of ultrapure water for dilution to obtain a hexadecyltrimethylammonium bromide solution; 9.6 mL of hexadecyltrimethylammonium bromide solution, 75 μL of 0.01 M KI solution, 80 μL of 25.4 mM chloroauric acid solution and 20.3 μL of 0.1 M NaOH solution were mixed to obtain a mixed solution; (2) Add 80 μL of 0.1 M ascorbic acid solution to 9.5 mL of the mixed solution with stirring at a speed of 700 rpm. The added ascorbic acid reduces Au(III) to Au(I). When the color of the solution changes from light yellow to colorless, add 10 μL of 0.1 M NaOH solution. After shaking for 1-2 seconds, the solution changes from colorless to blue, thereby obtaining a nano-triangular gold catalyst dispersion. (3) The nanotriangular catalyst dispersion was allowed to stand for 30 h to allow the nanotriangular gold particles to self-assemble. The dispersion was centrifuged and resuspended twice to remove irregular impurities and unreacted products. After centrifugation, the precipitate was collected to obtain the nanotriangular gold catalyst AuTNs.

[0040] The structure of the nano-triangular gold catalyst prepared in this example was characterized. Figure 1-Figure 3 shown.

[0041] Depend on Figure 1 and Figure 2 It can be seen that the nano-triangular gold catalyst prepared by the present invention presents a triangular two-dimensional morphology with clear edges and uniform particle size, with an average side length of 67.3 nm. It can be seen that the selective growth of the crystal face during the synthesis of the nano-triangular gold catalyst is well controlled. Figure 3 It can be seen that the characteristic diffraction peak of gold should appear in the XRD spectrum, 38.2° (corresponding to the {111} crystal plane), and compared with other crystal planes, the diffraction peak intensity of the {111} crystal plane is usually higher, indicating that the {111} crystal plane of the particle has preferential growth. The appearance of the strong peak of the {111} crystal plane in the XRD spectrum can prove the anisotropic crystal growth of the nano-triangular gold catalyst. At the same time, the width of the diffraction peak is narrow, indicating that the particles have high crystallinity.

[0042] Example 2: Preparation of nano-triangular gold catalyst AuNTs (1) Add 1.5 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution to 8 mL of ultrapure water for dilution to obtain a hexadecyltrimethylammonium bromide solution; 9.5 mL of hexadecyltrimethylammonium bromide solution, 70 μL of 0.01 M KI solution, 80 μL of 25.4 mM chloroauric acid solution, and 20 μL of 0.1 M NaOH solution were mixed to obtain a mixed solution; (2) Add 80 μL of 0.1 M ascorbic acid solution to 9 mL of the mixed solution with stirring at a speed of 700 rpm. The added ascorbic acid reduces Au(III) to Au(I). When the color of the solution changes from light yellow to colorless, add 10 μL of 0.1 M NaOH solution. After shaking for 1-2 seconds, the solution changes from colorless to blue, thereby obtaining a nano-triangular gold catalyst dispersion. (3) The nanotriangular catalyst dispersion was allowed to stand for 24 h to allow the nanotriangular gold particles to self-assemble. The dispersion was centrifuged and resuspended twice to remove irregular impurities and unreacted products. After centrifugation, the precipitate was collected to obtain the nanotriangular gold catalyst AuTNs.

[0043] Example 3: Preparation of nano-triangular gold catalyst AuNTs (1) Add 1.8 mL of 0.1 M hexadecyltrimethylammonium bromide stock solution to 8 mL of ultrapure water for dilution to obtain a hexadecyltrimethylammonium bromide solution; 9.8 mL of hexadecyltrimethylammonium bromide solution, 80 μL of 0.01 M KI solution, 80 μL of 25.4 mM chloroauric acid solution, and 21 μL of 0.1 M NaOH solution were mixed to obtain a mixed solution; (2) Add 80 μL of 0.1 M ascorbic acid solution to 10 mL of the mixed solution with stirring at a speed of 700 rpm. The added ascorbic acid reduces Au(III) to Au(I). When the color of the solution changes from light yellow to colorless, add 10 μL of 0.1 M NaOH solution. After shaking for 1-2 seconds, the solution changes from colorless to blue, thereby obtaining a nano-triangular gold catalyst dispersion. (3) The nanotriangular catalyst dispersion was allowed to stand for 40 h to allow the nanotriangular gold particles to self-assemble. The dispersion was centrifuged and resuspended twice to remove irregular impurities and unreacted products. After centrifugation, the precipitate was collected to obtain the nanotriangular gold catalyst AuTNs.

[0044] Example 4: Preparation method of carbon dioxide electroreduction catalyst based on biomimetic proton rejection layer The nano-triangular gold catalyst AuNTs prepared in Example 1 and water were mixed at a material-liquid ratio of 1 g:1 mL to obtain a nano-triangular gold catalyst solution; The nano-triangle gold catalyst solution and 0.104 mM hexadecyltrimethylammonium chloride solution were mixed at a volume ratio of 1:1, and stirred for 30 minutes to obtain a modified solution; The above-mentioned diluted solution was evenly dropped on the surface of the gas diffusion electrode in an amount of 100 μL. After drying with a hair dryer, a working electrode was obtained. Pt was used as a counter electrode and Ag / AgCl was used as a reference electrode. The electrode was immersed in a 0.1M sulfuric acid solution and the constant potential was set to -0.5V (vs Ag / AgCl). Electrochemical deposition was performed at 25°C. After deposition for 20 minutes, a bionic proton exclusion layer was formed on the surface of the nanotriangular Au catalyst. The thickness of the bionic proton exclusion layer was 5nm, and a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer was obtained.

[0045] Example 5: Preparation method of carbon dioxide electroreduction catalyst based on biomimetic proton rejection layer The nano-triangular gold catalyst AuNTs prepared in Example 1 and water were mixed at a material-liquid ratio of 0.8 g:1 mL to obtain a nano-triangular gold catalyst solution; The nano-triangle gold catalyst solution and 0.207 mM hexadecyltrimethylammonium chloride solution were mixed at a volume ratio of 1:1, and stirred for 20 minutes to obtain a modified solution; The above-mentioned diluted solution was evenly drop-coated on the surface of the gas diffusion electrode with a drop amount of 90 μL. After drying with a hair dryer, a working electrode was obtained. Pt was used as a counter electrode and Ag / AgCl was used as a reference electrode. The electrode was immersed in a 0.1M sulfuric acid solution and the constant potential was set to -0.5V (vs Ag / AgCl). Electrochemical deposition was performed at 20°C. After deposition for 15 minutes, a bionic proton exclusion layer was formed on the surface of the nanotriangular Au catalyst, and a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer was obtained.

[0046] Example 6: Preparation method of carbon dioxide electroreduction catalyst of biomimetic proton rejection layer The nano-triangular gold catalyst AuNTs prepared in Example 1 and water were mixed at a material-liquid ratio of 1.2 g:1 mL to obtain a nano-triangular gold catalyst solution; The nano-triangle gold catalyst solution and 0.2 mM hexadecyltrimethylammonium chloride solution were mixed at a volume ratio of 1:1, and stirred for 40 minutes to obtain a modified solution; The above-mentioned diluted solution was evenly dropped on the surface of the gas diffusion electrode with a drop amount of 110 μL. After drying with a hair dryer, a working electrode was obtained. Pt was used as a counter electrode and Ag / AgCl was used as a reference electrode. The electrode was immersed in a 0.1M sulfuric acid solution and the constant potential was set to -0.5V (vs Ag / AgCl). Electrochemical deposition was performed at 27°C. After deposition for 25 minutes, a bionic proton exclusion layer was formed on the surface of the nanotriangular Au catalyst to obtain a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer.

[0047] Test Example 1: Electrochemical Performance The carbon dioxide electroreduction catalyst based on the biomimetic proton-repelling layer prepared in Example 4 and the nano-triangular gold catalyst prepared in Example 1 were used to prepare working electrodes to construct an electrolytic cell system for electrochemical reduction of CO 2 The above electrolytic cell is used for electrochemical reduction of CO 2 When CO 2 The electric field strength of the electrolytic cell system was adjusted to 1.2×10 8 V / m for 30 min, and then electrochemical reduction of CO was performed at a potential of -1.0 V. 2 Among them, CO 2 The purity of the gas is 99.999% and the flow rate is 20cm 3 / min; electrochemical reduction of CO 2 The reaction temperature was 25 °C and the reaction time was 100 h. The effective current density and Faraday efficiency (FE CO ) to reflect the electrochemical performance, the results are as follows Figure 5 shown.

[0048] Wherein, the preparation method of the working electrode is: (1) 406 μg of the carbon dioxide electroreduction catalyst based on the biomimetic proton exclusion layer prepared in Example 4 and the nano-triangular gold catalyst prepared in Example 1 were dispersed in 500 μL of hexadecyltrimethylammonium bromide solution to obtain a catalyst solution; 80 μL of a 5 wt% Nafion solution was added to 2 mL of the catalyst solution as a binder to improve the adhesion of the catalyst on the electrode surface, and 3 mL of isopropanol was added to promote dispersion uniformity, and ultrasonic stirring was performed for 20 min to obtain a catalyst ink; (2) A 10 cm × 10 cm gas diffusion electrode (GDE) was selected as the electrode substrate, which was washed alternately with deionized water and isopropanol three times, and then dried at 60 °C for use; Use a sprayer to spray the catalyst ink onto the surface of the electrode substrate. The spraying amount is 10 μL each time. Evenly distribute the coating and dry it. Repeat the spraying 3-5 times until the loading amount of the catalyst ink on the electrode substrate reaches 0.5 mg / cm². Then, place the coated electrode to dry naturally at room temperature for 30 minutes, and then dry it at 50°C for 1 hour to ensure that the solvent is completely evaporated and the catalyst is firmly attached to the electrode surface to obtain a working electrode.

[0049] The electrochemical performance parameter detection method is as follows: Total current density (j total ) is as follows: apply a fixed working voltage and record the corresponding current (I 测量 ), the total current density is calculated by formula (I).

[0050] j 总 = I 测量 / A 电极 Formula (I); In the formula, j 总 is the total current density, I 测量 To measure the current, A 电极 is the effective area of ​​the working electrode.

[0051] The detection steps of Faraday efficiency are as follows: connect the gas phase outlet of the electrolytic cell to a gas chromatograph (GC) to detect the gas phase product in real time; calculate the molar amount of CO generated by the standard gas calibration curve based on the CO signal peak area measured by GC. n CO , and then use formula (II) to calculate the Faraday efficiency; FE CO =[ z ×F× (n CO / Q total )] 100% formula (II); Where z is the number of electrons transferred (CO generation corresponds to 2 electrons), F is the Faraday constant, which is 96485 C / mol, and n CO is the molar amount of CO produced, in mol, Q total is the total charge, in units of C, and its calculation formula is shown in formula (III), Q total = ∫I(t)dt Formula (III).

[0052] The calculation formula of effective current density is shown in formula (IV): Effective current density (j CO ) = total current density (j 总 )×Faraday efficiency (FE CO ) Formula (IV).

[0053] pass Figure 5 It can be seen that at the same potential, the carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer prepared in the present invention has j CO The absolute value is significantly higher than that of the nanotriangular gold catalyst, especially at more negative potentials (such as -1.1 V and -1.0 V). This indicates that the biomimetic proton-repelling layer enhances the CO generation ability of the catalyst. j CO The absolute value of increases with the decreasing potential, indicating that a more negative potential is conducive to the CO generation reaction. The biomimetic proton-repelling layer may regulate the local electric field on the catalyst surface or improve the CO 2 The combination with the active site improves the electron transfer efficiency of the reaction, thereby improving CO pass Figure 5 B It can be seen that at all potentials, the FE of the carbon dioxide electroreduction catalyst based on the biomimetic proton exclusion layer prepared in the present invention is CO Significantly higher than the nano-triangular gold catalyst. The CO2 electroreduction catalyst based on the biomimetic proton exclusion layer achieves the best FE at -1.1 V and -1.0 V CO (about 97% and 90%), while the highest FE of nanotriangular gold catalyst CO Only about 40%. The biomimetic proton exclusion layer is modified by increasing CO 2 The local concentration of the molecule inhibits the byproduct H 2 The selectivity of CO is improved.

[0054] Test Example 2: Stability The carbon dioxide electroreduction catalyst based on the biomimetic proton-repelling layer prepared in Example 4 was used to prepare a working electrode to construct an electrolytic cell system for electrochemical reduction of CO 2 The above electrolytic cell was operated for 100 h, and the total current density (j total ) and Faraday efficiency (FE CO ) to reflect stability, the results are as follows Figure 6 shown.

[0055] Depend on Figure 6 It can be seen that after long-term electrolysis for 100 hours, the total current density of the carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer prepared by the present invention remains stable, and the Faraday efficiency of CO is basically maintained above 95%, indicating that the catalyst has good long-term stability.

[0056] Test Example 3: In this test example, the concentration of the bionic proton exclusion layer is adjusted to obtain bionic proton exclusion layers with different charge densities, so as to analyze the electrochemical performance of the carbon dioxide electroreduction catalyst based on the bionic proton exclusion layer corresponding to the bionic proton exclusion layer with different densities. The charge density of the bionic proton exclusion layer is -100, 0, 100, 10000, 20014C / cm 3 , the results are as follows Figure 7 shown.

[0057] By Figure 7 As can be seen from A, at -1.0 V (relative to RHE), as ρ increases, the H outside the surfactant layer + The migration rate is reduced, which indicates that the cationic surfactant layer can screen the electric field and thus reduce the H + The charge of the surfactant layer also affects the local pH near the cathode. The pH distribution and proton concentration of surfactant layers with different charge characteristics at -1.0 V (relative to RHE) in a pH 1.0 electrolyte are shown in Figure 2. Figure 7 B. When the surfactant layer is uncharged, the pH in the range of 2 nm to 22.1 μm of OHP is higher than the bulk pH due to concentration polarization. However, within 2 nm of the OHP, the pH is lower than the bulk pH because protons are electrostatically attracted to the cathode. Figure 7 C further shows the pH at OHP under different electrode potentials. When the surfactant layer is neutral or negatively charged, a negative shift in electrode potential does not significantly increase the pH at OHP. In contrast, when the positive charge density of the surfactant layer is greater than +1000 C·cm −3 When the pH in the surfactant layer rises rapidly ( Figure 7 B), and as the electrode potential shifts negatively below −0.4 V (vs. RHE), the local pH at the OHP increases ( Figure 7 C). It is worth noting that when the charge density exceeds +10000 C·cm −3 When the cathode is covered with a cationic surfactant layer, the pH at OHP exceeds the bulk pH in the potential region below -0.4 V (vs. RHE). + The reduction-driven OHP local pH increase occurs only when the cation charge is 30000C cm -3 After that, the ability to repel protons decreases, which may be due to the stacking effect of the surfactant, resulting in changes in the surface microenvironment.

[0058] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A carbon dioxide electroreduction catalyst based on a biomimetic proton-repelling layer, characterized in that: It comprises a bionic proton exclusion layer and an active substance coated inside the bionic proton exclusion layer, wherein the active substance is a nano-triangular gold catalyst, and the bionic proton exclusion layer is prepared from a cationic surfactant.

2. The carbon dioxide electroreduction catalyst based on the biomimetic proton rejection layer according to claim 1, characterized in that: The cationic surfactant is hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide or polydimethyldiallylammonium chloride.

3. The carbon dioxide electroreduction catalyst based on the biomimetic proton rejection layer according to claim 1, characterized in that: The charge density of the bionic proton repelling layer is 10000-20014C / cm 3 .

4. The carbon dioxide electroreduction catalyst based on a biomimetic proton rejection layer according to claim 1, characterized in that: The nano-triangular gold catalyst is prepared by the following method: (1) mixing the hexadecyltrimethylammonium bromide solution, the KI solution, the chloroauric acid solution and the NaOH solution to obtain a mixed solution; (2) adding ascorbic acid solution to the mixed solution, and then adding NaOH solution until the solution becomes colorless to obtain a gold nanotriangle catalyst dispersion; (3) After the nano-triangular catalyst dispersion is allowed to stand, it is purified and centrifuged, and the precipitate after centrifugation is collected to obtain the nano-triangular gold catalyst AuNTs.

5. The carbon dioxide electroreduction catalyst based on the biomimetic proton rejection layer according to claim 4, characterized in that: In step (1), the volume ratio of hexadecyltrimethylammonium bromide solution, KI solution, chloroauric acid solution and NaOH solution is (9.5-9.8) mL: (70-80) μL: 80 μL: (20-21) μL; the concentration of KI solution is 0.01 M, the concentration of chloroauric acid solution is 25.4 mM, and the concentration of NaOH solution is 0.1 M.

6. The carbon dioxide electroreduction catalyst based on a biomimetic proton-repelling layer according to claim 4, characterized in that: In step (2), the volume ratio of the mixed solution, ascorbic acid solution and NaOH solution is (9-10) mL:80 μL:10 μL; the concentration of the ascorbic acid solution is 0.064 M, and the concentration of the NaOH solution is 0.1 M.

7. The carbon dioxide electroreduction catalyst based on a biomimetic proton rejection layer according to claim 4, characterized in that: In step (3), the standing time is 24-40 hours.

8. The method for preparing a carbon dioxide electroreduction catalyst based on a biomimetic proton rejection layer according to any one of claims 1 to 7, characterized in that: The following steps are involved: Dissolving the nano-triangular gold catalyst in deionized water to obtain a nano-triangular gold catalyst solution; The nano-triangular gold catalyst solution and the cationic surfactant solution are mixed and stirred to obtain a modified solution; then, a bionic proton exclusion layer is formed on the surface of the nano-triangular Au catalyst through an electrochemical deposition method or a physical adsorption method, thereby obtaining a carbon dioxide electroreduction catalyst based on a bionic proton exclusion layer.

9. The method for preparing a carbon dioxide electroreduction catalyst based on a biomimetic proton rejection layer according to claim 8, characterized in that: The concentration of the nano-triangular gold catalyst solution is 0.8-1.2 g / mL, and the concentration of the cationic surfactant solution is 0.104-0.207 mM; the concentration of the nano-triangular gold catalyst solution is 0.8-1.2 g / mL, and the concentration of the cationic surfactant solution is 0.104-0.207 mM.

10. Use of the carbon dioxide electroreduction catalyst based on a biomimetic proton exclusion layer according to any one of claims 1 to 7 in electrochemical reduction of carbon dioxide.